Analysis of Customer Service Interpersonal Communication in Improving Customer Satisfaction (Study of Pt. Syariah People's Financing Bank Mitra Agro Usaha Bandar Lampung) - Elia Agustiana; Andistia Syifani (Formosa Journal of Multidisciplinary Research, 2022)
The purpose of this research is to find out whether there is a relationship between customer service interpersonal communication and customer satisfaction at PT. Sharia People's Financing Bank Agro-Business Partners Bandar Lampung, This type of research is qualitative using a descriptive method that functions to describe or give an overview of the object being examined through data or samples that have been collected. The informants of this research are customers of PT. Sharia People's Financing Bank Agro-Business Partners Bandar Lampung. Researchers directly involved in the field conduct interviews with customer service, conduct data selection to make summaries or brief descriptions, present data with a set of structured information so as to provide the possibility of drawing conclusions and taking action. The results of the study can be concluded that the effectiveness of interpersonal communication can increase customer satisfaction, meaning that customers will trust and tend to accept well the messages conveyed by people who have the effectiveness of interpersonal communication in providing services, with that feeling comfortable and feeling valued, will generate interest. to be motivated, because the sociability of a communicator who has the ability to communicate effectively can attract customers to buy the products offered.